Descrivere l’indescrivibile. Il lessico di Plinio il Giovane nelle epistole sull’eruzione del Vesuvio [Describing the indescribable. The lexicon of Pliny the Younger in the epistles on the eruption of Vesuvius] - Edoardo Scarpanti (Open Journal of Humanities, 2021)
The article proposes a linguistic analysis of the two epistles of Pliny the Younger, addressed to the historian Tacitus, in which the author recalls and describes the catastrophic eruption of Vesuvius in the year 79 AD. Pliny had witnessed this event from Misenus, where he was dwelling with his uncle Pliny the Elder, and with his mother. The lexical choices made by the author, certainly not casual but rather carefully meditated and studied, in a complex rhetorical exercise (i.e. Asian style), draw up a lexicon that is able to describe what is normally difficult to describe. The lack of adequate signifiers, in fact, with respect to such an extraordinary fact must have forced Pliny to carefully choose the words to use, by isolating those that possessed precise semantic traits. In this way, he was able to build a “lexical reservoir of catastrophes” which, in all probability, inspired who later found themselves in the same need to tell in words what could hardly be told.